High Court Looks at Another Law Aimed at Online Pornography. - Palmer, Elizabeth A. (CQ Weekly, 2002)
On November 12, 2002, Supreme Court justices will deliberate the third case of its kind in which Congress tries to keep children from viewing indecent content on the World Wide Web. The 2000 law (PL 106-554) at issue stipulates that libraries have to obtain screening software for public computer terminals as a condition for getting federal aid available under two programs. Opponents to the law contend that such a requirement violates the constitutional right of free speech